2019
DOI: 10.3390/polym11091493
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organo-Sepiolite on the Morphological, Mechanical, and Rheological Properties of PP/ABS Blends

Abstract: To improve the poor impact toughness of polypropylene (PP), organo-sepiolite (O-Sep) filled 80/20 (w/w) polypropylene/poly(acrylonitrile-butadiene-styrene) (PP/ABS) nanocomposites were fabricated. The contents of O-Sep were correlated with the morphological, mechanical, and rheological behavior of PP/ABS/O-Sep blends. Scanning electron microscopy (SEM) was applied to study the morphology and thermogravimetric analysis (TGA) was applied to study the thermal stability. Differential scanning calorimetry (DSC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The thermal analysis results obtained in Fig. 7a, b are consistent with the results of similar materials prepared with polypropylene [38]. The thermal characteristics of the blend polymers obtained in the project are mostly close to the thermal behavior of polypropylene.…”
Section: Resultssupporting
confidence: 85%
“…The thermal analysis results obtained in Fig. 7a, b are consistent with the results of similar materials prepared with polypropylene [38]. The thermal characteristics of the blend polymers obtained in the project are mostly close to the thermal behavior of polypropylene.…”
Section: Resultssupporting
confidence: 85%
“…SiO 2 nanoparticles were modified by a conventional strategy with modifications according to our previous study. 41 The detailed experimental procedure was as follows: first, SiO 2 was washed three times with ultrapure water and dried at 60 °C for 12 h, followed by the addition of dried SiO 2 to HCl/H 2 O (v/v 1:7) and stirring at room temperature for 1 h. After the reaction was continued for 24 h, the mixture was washed three to five times with ultrapure water, followed by drying at 60 °C for 12 h to prepare acidified SiO 2 . Second, the silane coupler CG-570 was dissolved in ethanol/H 2 O (v/v 18:1), and the solution pH was adjusted to 4−6 with formic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, HNTs@AlPO 4 was obtained after centrifugation, washing, and drying. To improve the interfacial compatibility between inorganic particles and organic polymers, HNTs@AlPO 4 was modified by a silane coupling agent, CG-570, to obtain organically modified HNTs@AlPO 4 (o-HNTs@AlPO 4 ) using our previously modified method [ 31 ]. The detailed procedure is as follows: 0.5 g silane coupling agent CG-570 was added into 60 mL ethanol/H 2 O ( v / v 18:1) and the pH of the mixed solution was adjusted to 4–6 with formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Urquijo et al blended PLA/PBAT with different carbon nanotube (CNT) contents and demonstrated that CNTs selectively located in the PBAT phase induced the coalescence of PBAT spherical particles [ 19 ]. Our previous work demonstrated that sepiolite (Sep) improved the toughness of PP/ABS, enhanced both the mechanical and thermal properties of PP/PA6, and functions as a nucleating agent and compatibilizer between polymers [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%